2008
DOI: 10.1002/app.29387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of graft copolymers of syndiotactic polystyrene with polybutadiene and 4‐methylstyrene

Abstract: The basic method for synthesizing syndiotactic polystyrene-g-polybutadiene graft copolymers was investigated. First, the syndiotactic polystyrene copolymer, poly(styrene-co-4-methylstyrene), was prepared by the copolymerization of styrene and 4-methylstyrene monomer with a trichloro(pentamethyl cyclopentadienyl) titanium(IV)/modified methylaluminoxane system as a metallocene catalyst at 50 C. Then, the polymerization proceeded in an argon atmosphere at the ambient pressure, and after purification by extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…2, the characteristic peak (phenyl C-1 carbon at 144.3 ppm) in spectrum is strong and sharp confirming that the obtained copolymer is syndiotactic. Figure 2 shows the peak at 20.1 ppm derived from methyl carbon in p-methylstyrene units and the entire spectrum matches with those of sPSMS in previous reports [33,34].…”
Section: Polymerizationsupporting
confidence: 78%
“…2, the characteristic peak (phenyl C-1 carbon at 144.3 ppm) in spectrum is strong and sharp confirming that the obtained copolymer is syndiotactic. Figure 2 shows the peak at 20.1 ppm derived from methyl carbon in p-methylstyrene units and the entire spectrum matches with those of sPSMS in previous reports [33,34].…”
Section: Polymerizationsupporting
confidence: 78%
“…Figure 4(a) shows the peak at 20.1 ppm derived from methyl carbon in p-methylstyrene units and the entire spectrum matches with those of sPSMS in previous reports. 21,22 Characterization of sPSMS-graft-PDMS and Solvent Effect on the Degree of Graft. In order to investigate the effect of solvent on the degree of graft, the grafting reaction with hexamethylcyclotrisiloxane was carried out in two different solvents (THF and cyclohexane) under the same reaction condition.…”
Section: Resultsmentioning
confidence: 99%
“…E-mail: aaentezami@yahoo.com or aentezami@tabrizu.ac.ir blended with sPS. 22 Silicons of various microstructure and architecture are widely used in industry mainly because of their absence of toxicity, high chain flexibility and low surface energy. There are only a few reports concerning the synthesis of graft copolymers having polydimethylsiloxane and sPS by anionic ring-opening polymerization of hexamethylcyclotrisiloxane (D 3 ) from a side chain functionalized syndiotactic polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…6) reveal that EPs prepared using monoCp Zr alkoxide have a very low level of propylenepropylene repeating units (S aa ) comparing with EPs prepared using other metallocene catalysts. 16 The extremely low level of propylene-propylene repeating units indicates that EPs prepared by these new catalyst systems have a unique microstructure, which is characterized by its highly random EP distribution. This unique microstructure is highly desirable for EP rubber.…”
Section: Ethylene Polymerizationmentioning
confidence: 99%
“…[1][2][3] Utilization of various structures of Group 4 metal catalysts to provide effective polymer architectural control (e.g., molecular weight, 4,5 molecular weight distribution, 6,7 regiochemistry, [8][9][10] stereochemistry, [11][12][13][14] branching, [15][16][17] and chain end functionalization [18][19][20][21][22][23] ) has led to significant advancement in polymer chemistry. Studies have demonstrated that employing different structures of Group 4 metal catalysts in olefin polymerizations drastically affects the chain reaction pathways; 24,25 thus, specific polymer architectures can be obtained by the proper selection of Group 4 metal catalysts.…”
Section: Introductionmentioning
confidence: 99%